2017
DOI: 10.1002/cpdd.356
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acid‐Reducing Agents on the Pharmacokinetics of Palbociclib, a Weak Base With pH‐Dependent Solubility, With Different Food Intake Conditions

Abstract: Palbociclib free base capsule is a weak base drug with highly pH-dependent solubility. In vitro and in vivo studies evaluated the impact of acid-reducing agents on exposure of palbociclib and determined whether the impact, if any, can be mitigated by food. A drug-drug interaction study (study 1) was conducted first under fasted conditions and showed that coadministration of multiple doses of the proton-pump inhibitor rabeprazole substantially reduced palbociclib mean area under the concentration-time curve fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 27 publications
5
62
0
Order By: Relevance
“…The trial showed an average of 80% reduction in palbociclib C max in subjects stabilized with rabeprazole. The observed palbociclib C max for all subjects stabilized with rabeprazole were similar to that from the subgroup of subjects showing low exposure in other phase I trials . Furthermore, four subjects who showed low exposure receiving the palbociclib free base formulation alone demonstrated no further exposure change when receiving palbociclib in combination with rabeprazole…”
Section: The Case Of Palbociclibsupporting
confidence: 77%
See 4 more Smart Citations
“…The trial showed an average of 80% reduction in palbociclib C max in subjects stabilized with rabeprazole. The observed palbociclib C max for all subjects stabilized with rabeprazole were similar to that from the subgroup of subjects showing low exposure in other phase I trials . Furthermore, four subjects who showed low exposure receiving the palbociclib free base formulation alone demonstrated no further exposure change when receiving palbociclib in combination with rabeprazole…”
Section: The Case Of Palbociclibsupporting
confidence: 77%
“…When the pH is <4.3, the solubility of palbociclib is >0.5 mg/mL, which means that 125 mg of palbociclib free base can be completely dissolved in 250 mL of buffer. However, the solubility drastically decreases when the pH increases, approaching zero near pH 7 . Along with the solubility changes, the dissolution rate and extent, as illustrated in Figure a , are significantly decreased when pH increases.…”
Section: The Case Of Palbociclibmentioning
confidence: 93%
See 3 more Smart Citations